A statistical model for under- or overdispersed clustered and longitudinal count data - Grunwald, Gary K.; Bruce, Stephanie L.; Jiang, Luohua; Strand, Matthew; Rabinovitch, Nathan (Biometrical journal, 2011)
We propose a likelihood‐based model for correlated count data that display under‐ or overdispersion within units (e.g. subjects). The model is capable of handling correlation due to clustering and/or serial correlation, in the presence of unbalanced, missing or unequally spaced data. A family of distributions based on birth‐event processes is used to model within‐subject underdispersion. A computational approach is given to overcome a parameterization difficulty with this family, and this allows use of common Markov Chain Monte Carlo software (e.g. WinBUGS) for estimation. Application of the model to daily counts of asthma inhaler use by children shows substantial within‐subject underdispersion, between‐subject heterogeneity and correlation due to both clustering of measurements within subjects and serial correlation of longitudinal measurements. The model provides a major improvement over Poisson longitudinal models, and diagnostics show that the model fits well.